2019
DOI: 10.1055/s-0039-1677914
|View full text |Cite
|
Sign up to set email alerts
|

A Broader Look: Camera-Based Vital Sign Estimation across the Spectrum

Abstract: Objectives: Camera-based vital sign estimation allows the contactless assessment of important physiological parameters. Seminal contributions were made in the 1930s, 1980s, and 2000s, and the speed of development seems ever increasing. In this suivey, we aim to overview the most recent works in this area, describe their common features as well as shortcomings, and highlight interesting “outliers”. Methods: We performed a comprehensive literature research and quantitative analysis of papers publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 140 publications
0
35
0
1
Order By: Relevance
“…The applications of these sensors are monitoring of neonates in neonatal intensive care units, monitoring of heart rate during regional anesthesia, during dialysis and in the post-anesthesia care units. [9] Since the RGB camera records the facial features of the patient, there may be violations of privacy. Due to the same issue, the device can't be installed in the toilet or shower room.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of these sensors are monitoring of neonates in neonatal intensive care units, monitoring of heart rate during regional anesthesia, during dialysis and in the post-anesthesia care units. [9] Since the RGB camera records the facial features of the patient, there may be violations of privacy. Due to the same issue, the device can't be installed in the toilet or shower room.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that respiratory pattern can be reconstructed with a motion based method (37), which enables estimation of respiratory effort. Many other works have described attempts to derive physiology from video cameras, and an extensive comparison of the literature can be found in (38). In particular, the authors note that many approaches have been described in this field and that 'the lack of standardization hinders comparability of these techniques and of their performance'.…”
Section: Respiratory Effort Estimationmentioning
confidence: 99%
“…With increased computational power, camera-based vital sign monitoring is becoming more evident [10]. Not only for motion analysis but also for color measures, such as with PPGI, video forms an inexpensive sensing technology.…”
Section: Integrating Additional Medical Sensorsmentioning
confidence: 99%